2011
DOI: 10.1016/j.jvs.2010.08.060
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of peripheral arterial disease using stem and progenitor cell therapy

Abstract: Peripheral arterial disease (PAD) is a highly prevalent atherosclerotic syndrome associated with significant morbidity and mortality. PAD is most commonly caused by atherosclerosis obliterans (ASO) and thromboangiitis obliterans (TAO), and can lead to claudication and critical limb ischemia (CLI), often resulting in a need for major amputation and subsequent death. Standard treatment for such severe cases of PAD is surgical or endovascular revascularization. However, up to 30% of patients are not candidates fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
113
0
5

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(120 citation statements)
references
References 56 publications
0
113
0
5
Order By: Relevance
“…patients with ischemic disorders such as peripheral artery disease or in individuals having a recent, acute ischemic event such as myocardial infarction (1,5). However, high rates of cell death and ineffective cell engraftment have plagued these otherwise promising transplantation trials (3).…”
Section: Number Of Viable Epcsmentioning
confidence: 99%
“…patients with ischemic disorders such as peripheral artery disease or in individuals having a recent, acute ischemic event such as myocardial infarction (1,5). However, high rates of cell death and ineffective cell engraftment have plagued these otherwise promising transplantation trials (3).…”
Section: Number Of Viable Epcsmentioning
confidence: 99%
“…Это касается применения мононуклеарной фракции клеток аутологичного кост-ного мозга или периферической крови [98] и высоко-очищенных фракций эндотелиальных клеток-предше-ственников (CD133 + клетки) и CD34 + гемопоэтических СК [99,100]. Терапия заболеваний периферических ар-терий мононуклерными фракциями клеток костного мозга или периферической крови (после мобилизации Г-КСФ) оказалась более успешной, чем использование вышеупомянутых высокоочищенных гемопоэтических СК [100].…”
Section: результаты клинических исследований клеточной терапии ишемииunclassified
“…Однако они выполнены на небольшом числе пациентов и не позволяют сделать обоснованное заключение. Важно иметь в виду, что пациенты, нуждающиеся в терапевти-ческой неоваскуляризации, часто имеют сопутствующие кардиоваскулярные факторы риска, и применение у них клеточной терапии может сопровождаться негативны-ми реакциями, такими как кровотечения или тромбо-образование [98]. Клеточная терапия у таких больных может не оказать ожидаемого положительного эффекта вследствие снижения числа СК или их регенераторного потенциала [106][107][108].…”
Section: актуальные вопросы хирургических болезнейunclassified
“…Symptoms of CLI include pain at rest, ulceration and gangrene. Amputation of the affected limb is necessary in approximately 30% of cases and prognosis following amputation is bleak, with a mere 30% survival rate within five years [1][2]. Treatment often requires invasive revascularisation procedures, which are not suitable for a significant percentage of patients.…”
Section: Introductionmentioning
confidence: 99%
“…To date, clinical trials investigating the safety and efficacy of pro-angiogenic therapy in PAD patients including gene, growth factor or cell-based therapies have found that treatments were generally well tolerated but that efficacy was modest or inconsistent, a fact which has been partially attributed to incomplete knowledge of appropriate doses, duration of dosage and delivery methods. Current strategies have not yet resulted in satisfactory clinical efficacy and the use of single pro-angiogenic agents does not appear sufficient to adequately drive the complex vascularisation process in humans [1,[4][5]. The co-delivery of more than one agent has been shown to produce synergistic increases in pro-angiogenic efficacy in pre-clinical models of CLI [6][7].…”
Section: Introductionmentioning
confidence: 99%